Trading Systems and Growth Process in ASEAN-5 Economics - Onwuka, Kevin Odulukwe (2004)
This study centers on the analysis of effect of two main trade relations - multilateral and regional trade liberalizations, on the macroeconomic variables (GDP growth rates, foreign direct investment, and wage rate) of five ASEAN countries namely Malaysia, Indonesia, the Philippines, Singapore and Thailand. The study covers the period 1976- 2000. Endogenous growth model built on the framework of Bronsztein et al. (1998) is utilized and Generalised Least Square (GLS) fixed effects estimation technique is applied to estimate the parameters. Convergence hypothesis is also tested in the data. Four measures of trade liberalisation - trade share, Dollar's exchange rate distortion, average tariff and regional trade arrangement (RTA) dummy for participation regional trade arrangements, are constructed. The main results are that multilateral trade liberalisation and participation in regional trade arrangement lead to faster growth rate. This implies that maintaining stable exchange rate, tariff on selected key products, and high trade share boost economic iii [ a ~ growth in ASEAN region. Regional groupings could be utilized to achieve stable economic growth. Other important determinants of the cross-country growth rates are wage rate, employment level and FDI emphasizing the importance of incentives to workers and technology to improve total factor productivity per worker. Also multilateral trade liberalisation accelerates FDI, while regional trade liberalisation decelerates it. Other factors that influence the location of FDI in the regional economies are wage rate (low labour cost), employment level, human capital and initial GDP. Market size is not an important factor in the location of FDI in ASEAN countries in the regional and multilateral trading system. Where it is significant, its effect is negative. There is no noticeable effect of multilateral trading system on wage rate but regional trade liberalisation has. The most important determinants of wage rate in ASEAN region are GDP growth rates and FDI and employment level in both trade liberalisations. The impact of multilateral trading system on total factor productivity is positive with exchange rate distortion index and negative with average tariff. Regional trade liberalisation leads to low total factor productivity. The factors influencing total factor productivity are FDI, wage rate and export intensity in both trade liberalizations. Our data detect unconditional and conditional P - convergence. The conditional P -convergences in either trade liberalization 2re similar. This shows that ASEAN colintries can follow either of trading system to achieve the long run steady state equilibrium.